BANKING SECTOR MODERNIZATION(SPANISH RECIPE) - Timofey Malashenko (Ибероамериканские тетради, 2017)
The aim of the research is to analyze transformation of the Spanish banking sector after the ﬁnancial crisis of the year 2008. The author examines a hypothesis that banking system played an important role in the development of Spain’s economy. Spain’s banking sector was substantially transformed during the economic crisis, and now serves as a prerequisite for development of Spain’s national economy during post crisis period